Research on Mechanical Properties and AC Dielectric Properties of PP-g-MAH/SEBS Composite - LI Lin; CHEN Meng-yang; LIU He-qian; YANG Xu; ZHAO Hong (Journal of Harbin University of Science and Technology)
In view of the poor dispersion of the elastomer caused by the incompatibility between the polypropylene matrix and the elastomer dispersion phase in the polypropylene insulated power cable insulation materials， according to the similarity compatibility theory， the polypropylene matrix was grafted with maleic anhydride through the UV irradiation grafting technology， which increased the polarity of the matrix phase， so that the dispersion of the elastomer in the polypropylene matrix was significantly improved. The elastic modulus of the grafted composite was reduced and the toughness of the composite was improved. UV irradiation grafting technology can effectively control the grafting rate and avoid the degradation of materials during the grafting process by adjusting the irradiation dose. At the same time， the grafting modification improves the breakdown strength of the polypropylene matrix material， and cooperates with the improvement of the dispersion of the elastomer to increase the breakdown strength of the grafting modified composite material， reducing the loss factor of the composite material.